ABUSE AGAINST THE ELDERLY PERSON: ANALYSIS OF THE INTERNAL CONSISTENCY OF INSTRUMENTS - Rodrigues, Renata Clemente dos Santos; Araújo-Monteiro, Gleicy Karine Nascimento de; Marcolino, Emanuella de Castro; Brandão, Bárbara Maria Lopes da Silva; Barbosa, Lindemberg Arruda; Moraes, Ronei Marcos de; Souto, Rafaella Queiroga (Cogitare Enfermagem, 2023)
Objective: to evaluate the internal consistency of instruments used in Brazil to measure situations of violence against the elderly in two states. Method: a cross-sectional study with 481 elderly people in two different samples, states, and time periods. Two instruments were used to measure violence against the elderly person. The data was analyzed and the internal consistency between the items was measured by the Cronbach's alpha coefficient. Results: the Hwalek-Sengstock Elder Abuse Screening Test showed a coefficient of α = 0.08 for the sample collected in Paraíba, while in Pernambuco it was α = 0.57. The Conflict Tactics Scale was highly accurate in defining violence, with a coefficient of α = 0.81 and α = 0.80 for the two samples. Conclusions: only the Conflict Tactics Scale turned out to be reliable and stable for determining physical and psychological violence among the elderly, thus contributing as a way of uncovering the phenomenon.